2020
DOI: 10.1016/j.jcsr.2020.106081
|View full text |Cite
|
Sign up to set email alerts
|

On the strength of stainless steel fillet welds

Abstract: This paper describes 24 tests performed on welded specimens made of 3 stainless steel grades: EN 1.4307 (304L) and EN 1.4404 (316L) austenitic grades and EN 1.4062 duplex grade. For each grade, tests were carried out parallel to the weld and along the transverse direction. The austenitic grades were welded using GMAW (MAG), while the duplex grades were welded using Gas Metal Arc Welding (GMAW) and Gas Tungsten Arc Welding (GTAW or TIG). After failure, the fracture surfaces were measured using Digital Image Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…However, in the literature [18], it was shown that the effect of the mechanical properties of the welding consumable has an influence on the strength ratio. It is also evidenced herein by the comparison of the strength ratios of both austenitic grades showing an average strength ratio of 1.01 and 1.16 for the longitudinal direction for respectively the EN 1.4307 and 1.4404 grade, while both base metals exhibit very similar stress-strain behaviour [11].…”
Section: Assessment Of the Design Rulessupporting
confidence: 59%
See 3 more Smart Citations
“…However, in the literature [18], it was shown that the effect of the mechanical properties of the welding consumable has an influence on the strength ratio. It is also evidenced herein by the comparison of the strength ratios of both austenitic grades showing an average strength ratio of 1.01 and 1.16 for the longitudinal direction for respectively the EN 1.4307 and 1.4404 grade, while both base metals exhibit very similar stress-strain behaviour [11].…”
Section: Assessment Of the Design Rulessupporting
confidence: 59%
“…The Vickers hardness measurements showed a relative constant hardness level in the base metal and weld metal with a maximum difference of 8%. More information on the welding procedure and the subsequent quality assessment can be found in [11].…”
Section: Welding Process and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Microstructural investigation was then achieved by cutting, polishing and etching the welded samples (see ferrite in dark and austenite in white contours in Figure 2). The microscopic images taken in the base metal (BM), heat affected zone (HAZ) and fusion zone (FZ) were processed according to ASTM E562, and the resulting ferrite content was compared to the recommendations as shown in Table 1 [13].…”
Section: Fabrication and Welding Parametersmentioning
confidence: 99%